Analisis Degradasi Permukaan Bahan Isolasi Resin Epoksi dengan Pengisi Pasir Pantai yang Mengandung Banyak Kalsium - Moh Toni Prasetyo; Hamzah Berahim; T. Haryono (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2012)
Insulation materials that commonly used in air insulation, which, is operated at high voltage, are the porcelain, glass, and polymer materials. One of the insulating polymer materials that are used is epoxy resin because it has several advantages compared to porcelain and glass. However, this insulation material has a shortage of aging/degradation of the surface (surface-aging) due to environmental pollution. Environmental pollution can cause insulation coated with dirt and chemicals in the long time.Material that was used in this research was epoxy resin polymer isolation using of comparison values (base material diglycidyl ether of bisphenol-A (DGEBA) : hardener material or curing agent metaphenylene diamine (MPDA)) were 1:1, with the increase of silane and coastal sand as filler by the value of 10%, 20%, 30%, 40%, and 50%, sample size was 120 x 50 mm.Research was done in laboratory according to standard IEC 587: 1984. High voltage electrodes were connected to high voltage AC generator 3.5 KV, and NH4CI contaminants flowing on insulator surface of 0.3 ml / min from high voltage electrode. The ground electrode was connected to oscilloscope for measuring the leakage current. In this study, the effect of variation in stoichiometry to the hydrophobic contact angle value, leakage current waveforms, and surface degradation caused by erosion and tracking processes and tracking time were analyzed.From the results of the research, it was obtained that the epoxy resin that was used in this research are categorized as hydrofobik and partially wetted. The increase concentration of silane dan coastal sand as filler caused the increase in contact angle which meant the increase in surface insulation resistance, so that leakage currents flew on the surface insulating material not easily. The increase in concentration of silane dan coastal sand as filler retarded the carbon growth the surface of insulating material. This indicated that the increase in filler concentration slow down the aging or the degradation decreasing on the surface of insulating material. Concentration value of filler that had the optimal performance of the tracking process and erosion was 40%.